A társadalmi vállalkozások és tevékenységeik ismertsége, illetve az előttük álló feladatok egy kérdőíves felmérés eredményei alapján = Visibility of social enterprises and their activities and duties based on the results of a questionnaire - Péter, Zsolt (Közép-Európai Közlemények, 2018)
Social enterprise as a concept can be considered as relatively new in the Hungarian and International literature, even though it is a long-standing phenomenon. However uniform, widely accepted definition does not exist, recent domestic researches in the area have helped to clarify the concept. An exciting research question is how social enterprises are thinking about their goals, framework of their activities, available financial sources, and future opportunities. During their inquiries it became apparent that the social embeddedness of the sector and the visibility of their activities require further research, so it needs to understanding the opinions of people too. First in my study I will describe the results of the questionnaire than I try to collect all the possible tasks connected to their products/services, prices, market places, and promotions.